Edukasi dan Deteksi Dini Sebagai Upaya Promotif dan Preventif dalam Pengendalian Penyakit Tidak Menular - Intan Kumalasari; Maksuk; Faiza Yuniati; Maliha Amin; Hendawati (Universitas Medan Area, 2023)
One of the efforts to support the transformation of the Health sector is by implementing the first pillar, namely primary services that focus on promotive (education) and preventive (prevention and early detection efforts). This effort is very effective in reducing morbidity and mortality in the community, especially those caused by non-communicable diseases. Non-communicable diseases (NCD) are responsible for at least 70% of deaths in the world. Even though it cannot be transmitted from person to person or from animal to person, weak control of risk factors can affect the increase in cases every year. One of the non-communicable diseases is hypertension. The purpose of this community service is to carry out early detection and provide education and health services to the 3-4 Ulu sub-district community about risk factors that can increase blood pressure and their prevention efforts. This activity was carried out on Saturday 30 July 2022 at 08.00-13.00 WIB and was attended by 60 residents. The method of this activity is early detection in the form of blood pressure checks, risk factor screening, counseling and health services. This activity was considered successful, based on the enthusiasm of the participants who attended exceeded the target, the desire to ask questions and have their blood pressure checked, to be able to mention risk factors and disease prevention efforts as well as feedback from participants who stated this counseling was considered interesting and useful.